2009
DOI: 10.1002/ijc.24355
|View full text |Cite
|
Sign up to set email alerts
|

An integrated humoral and cellular response is elicited in pancreatic cancer by α‐enolase, a novel pancreatic ductal adenocarcinoma‐associated antigen

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a fatal disease with a very poor 5-year survival rate. a-Enolase is a glycolytic enzyme that also acts as a surface plasminogen receptor. We find that it is overexpressed in PDAC and present on the cell surface of PDAC cell lines. The clinical correlation of its expression with tumor status has been reported for lung and hepatocellular carcinoma. We have previously demonstrated that sera from PDAC patients contain IgG autoantibodies to a-enolase. The present work was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
125
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 50 publications
3
125
0
Order By: Relevance
“…5 Sera collected 2 weeks after 3 rounds of vaccination were diluted 1:500 in phosphate-buffered saline (PBS) and antibody concentration was calculated by regression analysis using 8 two-fold serial dilutions of 1 g/mL of 72/1.11 monoclonal antibody (mAb) for a standard curve (kindly provided by P. Migliorini, University of Pisa, Pisa, Italy).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…5 Sera collected 2 weeks after 3 rounds of vaccination were diluted 1:500 in phosphate-buffered saline (PBS) and antibody concentration was calculated by regression analysis using 8 two-fold serial dilutions of 1 g/mL of 72/1.11 monoclonal antibody (mAb) for a standard curve (kindly provided by P. Migliorini, University of Pisa, Pisa, Italy).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…4 ENO1 is coded by the ENO1 gene, is overexpressed in the cytoplasm of PDA cells, and is also present on their membrane. 5 In the cytoplasm, ENO1 acts as a glycolytic enzyme, whereas on the membrane it acts as a plasminogen receptor and plays an important role in cell migration. 6,7 We have shown that patients with PDA with autoantibodies to ENO1 also present an ENO1-specific T-cell response that is not observed in patients with no ENO1 autoantibodies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In pancreatic cancer patients, the anti-ENOA autoantibodies are directed against phosphorylated Serine 419 (Tomaino et al, 2011). One study has shown that, in pancreatic cancer, ENOA elicits a CD4+ and CD8+ T cell response both in vitro and in vivo (Cappello et al, 2009). In pancreatic cancer patients, production of anti-ENOA IgG is correlated with the ability of T cells to be activated in response to ENOA (Cappello et al, 2009).…”
mentioning
confidence: 99%
“…One study has shown that, in pancreatic cancer, ENOA elicits a CD4+ and CD8+ T cell response both in vitro and in vivo (Cappello et al, 2009). In pancreatic cancer patients, production of anti-ENOA IgG is correlated with the ability of T cells to be activated in response to ENOA (Cappello et al, 2009). In patients with oral squamous cell carcinoma, an HLA-DR8-restricted peptide (amino acid residues 321-336) of human ENOA recognized by CD4+ T cell has been identified (Kondo et al, 2002).…”
mentioning
confidence: 99%